Narrativas de mujeres indígenas de la etnia Sikuani víctimas de violencia doméstica y dinámicas socio familiares (2021)
The objective of this research is to analyze the narratives of adult indigenous women of the Sikuani ethnic group of the Cumariana community, which was developed from the qualitative model, with a narrative design and in-depth interviews were used for the collection of information. The research was conducted with theoretical references based on domestic violence, socio-family dynamics, ethnicity, identity and culture, the Sikuani community and the family. For the analysis of the results, three categories were proposed: domestic violence, socio-family dynamics and family, where subcategories were identified such as the meaning of domestic violence, consequences of domestic violence, ethnicity, identity, culture and extended family, which responded to the objectives proposed in the research. Likewise, an interpretation of the subcategories was made and as a result analysis it was found that the indigenous woman in her role possesses certain characteristics and meanings of domestic violence rooted in her culture and community, with evidence of psychological, emotional, economic and cultural effects in terms of her couple, family, social and cultural context.